Management of Renal Failure and Ascites in Patients with Cirrhosis - Kaushal Madan; Ashish Mehta (International Journal of Hepatology)
Ascites and renal dysfunction in cirrhosis occur when the liver disease is decompensated and signify the presence of advanced liver failure. However, the precipitating causes should be looked for and treated. Although liver transplantation is the treatment of choice in patients with advanced liver failure, mild to moderate ascites can be treated effectively with medical management. Similarly, renal failure in cirrhotics is reversible if the precipitating causes can be treated effectively and by use of combination of vasoconstrictors and albumin. Transjugular intrahepatic portosystemic shunts also offer an effective therapy for refractory ascites and HRS. Such treatments may offer effective bridge to liver transplantation, by improving short and medium term survivals. Here, we shall discuss all the options available for the management of these complications of cirrhosis.